Growth performance and internal organs morphology of broiler chickens fed kenaf seed meal (2017)
Kenaf seed meal is a potential feed ingredient in poultry nutrition but little is known about its utilization in broiler diets. This study was carried out to examine the organ weights and intestinal morphology of broilers fed kenaf seed meal in combination with soya bean meal. Two hundred and forty birds were allotted to five treatments replicated six times with eight birds per replicate. The proximate composition of kenaf seed meal was determined, the broilers weight and feed intake were monitored. At six weeks of age, two birds were sacrificed per replicate and vital organs were carefully collected and weighed. Also, the villi width, height and crypt depth were measured. The results of the study show that kenaf seed meal was rich in crude protein (28%), gross energy (3,929Kca/Kg) and crude fibre (3.6%). It was observed that duodenal villi were more influenced than the ileal villi. Hence, the test diet was seemingly more absorbed in the duodenum region than in the ileum, suggesting effective nutrients utilization if offered at safe level.